Surgical Resection of a Liver Metastasis from Breast Cancer - Selvakumar, D (Ann R Coll Surg Engl, 2015)
We report a case of a solitary liver metastasis from breast cancer in a 65-year-old woman. The patient underwent a mastectomy and axillary lymph node clearance for right breast cancer in 1990. A solitary metastasis was found in the left lobe of the liver by ultrasonography, 20 years after the initial mastectomy. A left lateral segmentectomy was performed in January 2011 and adjuvant hormonal therapy was also initiated. At present, she remains disease free. This case demonstrates the implementation of liver resection to provide an effective treatment for metachronous metastatic breast cancer. We encourage surgeons to offer suitable patients this surgical treatment option, which is shown to provide a survival benefit.